Engineering Application In Fuzzy Multi – Objective Linear Programming Problems - Khaled Elsharkawy (International Journal of Advanced Science and Technology, 2020)
Multi-objective linear programming problems (MOLPP) have many applications in the field of science and engineering. In this paper, the neural network method was applied to the (MOLPP) in a large steel producing unit, SNS (Society National de Sederurgie) located in the city of Annaba, in Algeria. The MOLPP consists of ten objectives simultaneous maximization functions, subject to 35 linear constraints involving 15 decision variables